CdS : SiO2 nanocomposite as a luminescence-based wide range temperature sensor. Issue 90 (1st October 2015) - Saxena, Nupur; Kumar, Pragati; Gupta, Vinay
<x xml:space="preserve">Abstract</x> A wide range (20–560 K) temperature sensor exhibiting linear behavior in entire range is devised from CdS:SiO2 nanocomposite with average sensitivity and resolution ≈10−2 K−1 & 10−4 K respectively and maximum relative sensitivity ~8.4% K−1 at 120 K.​